Strong gender-specific additive effects of the NYD-SP18 and FTO variants on BMI values - Hubacek, J A; Dlouha, D; Lanska, V; Adamkova, V (Physiological research, 2015)
The role of the FTO gene in obesity development is well established in populations around the world. The NYD-SP18 variant has been suggested to have a similar effect on BMI, but the role of this gene in determining BMI has not yet been verified. The objective of our study was to confirm the association between NYD-SP18 rs6971019 SNP and BMI in the Slavic population and to analyze i) the gender-specific effects of NYD-SP18 on BMI and ii) the simultaneous effect of FTO rs17817449 and NYD-SP18 on BMI. We analyzed a sample of a large adult population based on the post-MONICA study (1,191 males and 1,368 females). Individuals were analyzed three times over 9 years. NYD-SP18 rs6971019 SNP is related to BMI in males (2000/1 GG 28.3+/-3.7 kg/m(2) vs. +A 27.5+/-3.7 kg/m(2) P<0.0005; in other examinations P<0.05 and <0.005), but not in females (all P values over 0.48 in all three examinations). Further analysis revealed the significant additive effect (but not the interaction) of FTO and NYD-SP18 SNPs on BMI in males (all P<0.01). These results suggest that association between NYD-SP18 rs6971019 SNP and BMI may be restricted to males. Furthermore, variants within NYD-SP18 and FTO genes revealed a significant additive effect on BMI values in males.
Keywords: dospělí; Female; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Obesity; lidé; Polymorphism, Single Nucleotide; Proteins; Sex Characteristics; Genetic Variation; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; proteiny; obezita; Male; pohlavní dimorfismus; index tělesné hmotnosti; lidé středního věku; gen pro FTO; mužské pohlaví; Body Mass Index; genetická variace; Middle Aged; Humans